Ekstrak metanolik biji duwet (Syzygum cumini L. (Skeels) untuk penghambatan kerusakan oksidatif pada emulsi minyak wijen [Methanolic extract of Java plum (Syzygium cumini L. (Skeels) seed to inhibit oxidative damages in sesame seed oil emulsion] - Rohadi Rohadi; Dewi Larasati; Sri Haryati (Kementerian Perindustrian, 2021)
Methanolic extract of Java Plum (Syzygium cumini) seed (MEJS) have strong antioxidant activity by radical scavenging antioxidant-2,2 diphenyl-1-picrylhydrazyl (RSA-DPPH) assay, ferric ion reducing antioxidant power (FRAP), also strong in the inhibition of lipid oxidation in the linoleic acid emulsion system assay, but moderate on striped catfish (Pangasius hypothalamus) oil-in-water emulsions. Antioxidant activity of MEJS is relatively stable on thermal heating by oven until 130 oC/10 minutes, gamma ray’s irradiation up to 12.5 KGy and suitable application on pH 6-9 acidity. MEJS is potential as a natural antioxidant in food system. However, must be carried out further assay the effectiveness of its use in commercial edible oil. The purpose of this research was to analyzed the effect of the addition of MEJS 200-1000 ppm against inhibition of lipid oxidation in an emulsion system. Research methods consisted of sesame seed oil extraction and analyzes of its a fatty acid profile, MEJS applied on sesame seed oil emulsion system to inhibit of lipid oxidation during 3 weeks storage. Assay variables were RSA-DPPH, the peroxide value (PoV), TBARs value and the free fatty acids (FFA) values changes. The result showed that 35.85% Sesame seed oil yield consisted of 11.62% saturated fatty acids, 6.23 % mono unsaturated fatty acids and 85.95% poly unsaturated fatty acids. Applied of MEJS (200-1000 ppm) could increase of DPPH• radical scavenging stronger than both BHT 200 ppm and the control (sesame seed oil bulky), but didn’t correlative impact with inhibition autoxidation on it. Applied MEJS > 800 ppm comparable with BHT 200 ppm. MEJS as a natural antioxidant is not appropriate to apply for the oil in water of emulsion system.